Biochemical Perturbations and Metabolic Derangements Induced by Benzophenone-3 at Environmentally Relevant Concentration in the Liver of Danio rerio - Miltonprabu , S.; Shagirtha , K.; Senthilmurugan , S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
UV filters are used daily by millions of people. many wastewater treatments plants are ill-equipped to filter them properly. As a result, UV filters are progressively reaching the environment at an alarming level. Benzophenone-3(BP3) in particular, are toxic to all organisms. Its toxic effects include coral bleaching and interference with metabolic, enzymatic, and reproductive activities. The present study aims to assess the toxic impact of environmentally relevant concentration of BP3(44μg/l) on some selected biochemical variables in the liver tissue of Zebra fish on different exposure periods. The exposed fishes were shown to exhibit significant alterations in the carbohydrate, lipid and protein levels and their metabolism and elevated the level of transaminases in the hepatic tissue. The severity of derangement was slowly increased upon increasing exposure period and more significant at the 45th days of exposure. From our results, it may suggested that BP3 exposure at sub chronic periods even at the environmentally relevant concentration might induce intense biochemical alterations in the liver of D.rerio.